1995
DOI: 10.1111/j.1745-9125.1995.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Messner and Rosenfeld's Institutional Anomie Theory: A Partial Test*

Abstract: In Crime and the American Dream, Messner and Rosenfeld contend that culturally and structurally produced pressures to secure monetary rewards, coupled with weak controls from noneconomic social institutions, promote high levels of instrumental crime. Empirically, they suggest that the effects of economic conditions on profit‐related crime depend on the strength of noneconomic institutions. This investigation evaluates this proposition with cross‐sectional data for U.S. states. In brief; the nonlinear models sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 32 publications
2
130
2
3
Order By: Relevance
“…Similarly, Chamlin and Cochran (1995), in a state-level test of institutional anomie, found that the effect of poverty on property crime decreased as voter turnout increased. Thus, these studies suggest that crime depends on the relative strengths of political and economic institutions.…”
Section: Politics In Previous Criminological Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Chamlin and Cochran (1995), in a state-level test of institutional anomie, found that the effect of poverty on property crime decreased as voter turnout increased. Thus, these studies suggest that crime depends on the relative strengths of political and economic institutions.…”
Section: Politics In Previous Criminological Researchmentioning
confidence: 97%
“…However a recent reformulation of anomie theory-institutional anomie theory-suggests that the impact of the economy on crime depends on the relative strengths of economic and non-economic institutions such as the polity Rosenfeld, 1997a, 1997b). Cross-national (Savolainen, 2000) and state-level research (Chamlin and Cochran, 1995) testing institutional anomie theory suggests that politics can have direct and conditional effects on crime. In addition, other recent research suggests that aspects of local politics such as the race of the mayor can have direct effects on interracial homicide (Jacobs and Wood, 1999), police killings of minorities (Jacobs and O'Brien, 1998) and violence against police (Jacobs and Carmichael, 2002).…”
Section: Biographical Sketchmentioning
confidence: 99%
“…Several prior structural-level studies have employed voter turnout to represent various concepts potentially related to crime and violence, including civic engagement (Chamlin and Cochran 1995;Rosenfeld, Messner, and Baumer 2001), political disaffection (Callahan 1998), and level of conformity with norms (Coleman 2002). For whom an electorate votes, however, may be an even more important indicator of larger social forces than voter turnout, especially in the midst of a political transition.…”
Section: Discussionmentioning
confidence: 99%
“…However, Thus, when social institutions -whether economic, political, or cultural -are threatened, strained or collapse, crime is more likely (Figure 2). The relationship between the strength of social institutions and aggregated crime rates is tested in different countries and for different crimes (Messner and Rosenfeld 1997;Chamlin and Cochran 1995;Piquero and Piquero 1998;Savolainen 2000;Maume and Lee 2003;Schoepfer 2004;Kim and Pridemore 2005;Bjerregaard and Cochran 2008;Stults and Baumer 2008). Overall, the studies reviewed tend to support the theory.…”
Section: Theoriesmentioning
confidence: 99%